MERAWAT KESEIMBANGAN: KAJIAN ETIKA PRIBADI DAN FALSAFAH TALLU LOLONA DALAM MENGHADAPI KRISIS EKOLOGI - Purba, Fredi Ardo; Paembongan, Raka Saden Priya L; Simangunson, Dion Carlos (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2025)
The Toraja community is facing an ecological crisis characterized by environmental degradation, such as declining water quality, loss of wildlife habitat, and deforestation. This crisis is mainly caused by drastic changes in land use that lead to exploitation due to the anthropocentric view of humans. The impact is not only on the environment but causes natural disasters, such as floods and landslides that are detrimental to human life. This research examines how personal ethical values contained in the Tallu Lolona philosophy can help overcome the crisis. This research was conducted using the literature study research method. The results showed that the Tallu Lolona philosophy emphasizes the harmonious relationship between humans, animals, and plants as part of a cosmology of mutual respect and care. Thus, Tallu Lolona philosophy can offer a personal ethic that views nature as a brother who must be protected and respected. It encourages a more harmonious relationship between humans and nature and promotes individual responsibility in maintaining ecological balance.